Psychological characteristics of university applicants` groups - Chugaeva, Nataliya (My University, 2021)
In the article is shown the result of empirical research of groups of applicants on the criterion of combining indicators of their social development as a collective subject of educational activity and applicant learning success was the derivation of empirical typology of effective and ineffective tutors (total four types: effective, pseudo-effective, formally effective and ineffective). У статті показано, що результатом емпіричного дослідження груп здобувачів за критерієм поєднання показників їх соціального розвитку як колективного суб’єкта навчальної діяльності та успішності навчання абітурієнтів стало виведення емпіричної типології ефективних і неефективних наставників (всього чотири типи: ефективні, псевдо-ефективний, формально ефективний і неефективний).
Keywords: кафедра гуманітарних дисциплін; teacher-mentor; group of applicants of higher education; educational socialization; педагог-наставник; група здобувачів вищої освіти; освітня соціалізація